URBAN PARKS AS INSTRUMENTS FOR SOCIO-ENVIRONMENTAL PLANNING AND PUBLIC POLICY: A SYSTEMATIC REVIEW - Bocks, Ana Paula Amambahy da Costa; de Souza, Katia Marisa Soares da Silva; Pierott, Rodrigo Moulin Ribeiro; Najjar, Mohammad K. (Seven Editora, 2026)
This study sought to analyze urban parks by assessing their contributions to sustainability, social justice, and community well-being. The research was conducted through a systematic review structured according to the PRISMA 2020 protocol, including bibliometric and bibliographic analyses of international databases (Scopus and Web of Science) covering the period from 2020 to 2025. The tools used included Rayyan for screening and duplicate exclusion; VOSviewer and Bibliometrix for bibliometric analysis; and Zotero, Mendeley, and Excel for reference management and organization. Five questions guided the study in order to achieve its objective: (i) which dimensions are addressed by recent research on sustainable urban parks? (ii) what are the main themes discussed within these dimensions? (iii) which methodologies and analytical tools have been applied? (iv) which conceptual and methodological gaps remain in the literature? and (v) which future research directions can be suggested? A total of 61 highly relevant articles were selected, confirming that parks function as instruments of social inclusion, health promotion, and mitigation of environmental impacts, while also fostering sustainability. In response to the proposed questions, the review showed that recent studies on urban parks have increased, particularly those addressing health, sociospatial justice, quality, management, and socioeconomic impacts, and discussing themes such as mental health, accessibility, green gentrification, and civic participation. Although diverse methodologies have been applied, gaps persist, including the limited number of longitudinal studies, differences between developed and developing countries, lack of maintenance and safety, and the absence of studies on the effects of parks as therapeutic spaces for neurodivergent populations. It is concluded that urban parks should be recognized as critical infrastructures for public health, social inclusion, and climate resilience.